Numerical simulation of three-dimensional double diffusive convection in a lid-driven cavity - Ghachem, Kaouther; Kolsi, Lioua; Maatki, Chemseddine; Alghamdi, Abdulaziz; Öztop, Hakan Fehmi; Borjini, Mohamed Naceur; Al-Salem, Khaled (Elsevier France-Editions Scientifiques Medicales Elsevier, 2016)
In this work, the heat and mass transfers in 3D lid driven cavity is analyzed. Double-diffusive convective flow in a cubic enclosure with moving left side in -y (Case I) or +y (Case II) directions is studied numerically. The cavity is heated from left side and cooled from right and constant different concentration is imposed, while remaining surfaces are adiabatic. The FVM based on the 3D vector-potential - vorticity formalism is used as numerical method. Prandtl number and Lewis number are fixed at 10, 0.7 and 2, respectively. The study covers a wide range for Richardson number 0.1 <= Ri <= 10 and Buoyancy ratio -10 <= Ri <= 10. Results are presented by particle trajectories, isotherms, Iso-concentration and local and mean Nusselt and Sherwood numbers. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: Double-diffusive convection; Fluid flow; Three dimensional; Lid-driven